2017
DOI: 10.1016/j.celrep.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Calbindin Levels in Hippocampal Excitatory Neurons Mediate Stress-Induced Memory Loss

Abstract: Calbindin modulates intracellular Ca dynamics and synaptic plasticity. Reduction of hippocampal calbindin levels has been implicated in early-life stress-related cognitive disorders, but it remains unclear how calbindin in distinct populations of hippocampal neurons contributes to stress-induced memory loss. Here we report that early-life stress suppressed calbindin levels in CA1 and dentate gyrus (DG) neurons, and calbindin knockdown in adult CA1 or DG excitatory neurons mimicked early-life stress-induced mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 46 publications
6
57
0
1
Order By: Relevance
“…Our previous studies have linked hippocampal nectin3 to early-life stress-induced spine loss and cognitive deficits [16,48]. As the first study to examine nectin3 in the PFC, we first confirmed that nectin3 is expressed in both excitatory and inhibitory neurons in mouse mPFC, similar to our findings in the hippocampus [30]. How nectin3 contributes to the stress effects on the neurodevelopment of the adolescent PFC is unknown.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our previous studies have linked hippocampal nectin3 to early-life stress-induced spine loss and cognitive deficits [16,48]. As the first study to examine nectin3 in the PFC, we first confirmed that nectin3 is expressed in both excitatory and inhibitory neurons in mouse mPFC, similar to our findings in the hippocampus [30]. How nectin3 contributes to the stress effects on the neurodevelopment of the adolescent PFC is unknown.…”
Section: Discussionsupporting
confidence: 84%
“…All of the behavioral tests were carried out between 09:00 and 16:00 as described previously [28,30,31]. Behavior in the open field was analyzed using ANY-maze 4.98 (Stoelting, Wood Dale, IL).…”
Section: Behavioral Testsmentioning
confidence: 99%
“…3g-i). These results are in line with recent findings suggesting alterations in inhibitory neuron networks that occur as a consequence of ELS [24,25]. In order to assess if these morphological and functional differences stemmed from persistent increases in corticosterone levels or if ELS mice were hyperreactive to stressful insults, we determined the concentration of corticosterone under basal conditions (between days of experimentation) and immediately following tube test encounters ( Supplementary Fig.…”
Section: Faster Resolution Of Social Conflicts In Animals That Experisupporting
confidence: 84%
“…We speculate that anxiolytic and anxiogenic information from pBLA and aBLA may be respectively integrated in vCA1 and/or may be further transmitted to distinct downstreams of vCA1 Calb1+ and vCA1 Calb1− neurons, by which they control whether and where to go or not to go when facing a complicated environment. Given that the excitatory neurons in the aBLA and pBLA could be telegraphed through mutual inhibition 19 and that Calb1+ neurons consist of excitatory neurons and GABAergic interneurons 31 , it will be interesting in future studies to determine whether aBLA-vCA1 and pBLA-vCA1 circuits influence each other and how their coordination ultimately occurs in a conflict environment. In addition, the BLA shares reciprocal projections with the vCA1 32,33 , and the vCA1-BLA circuit encodes contextual information in fear 33 .…”
Section: Discussionmentioning
confidence: 99%